1985
DOI: 10.1017/s0022215100097796
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the external auditory meatus and middle ear

Abstract: A staging system is suggested for carcinomas of the external and middle ear, based on a personal series of 47 patients. Statistical analysis showed that the proposed system was a valid method of identifying significant predictor factors. Other significant predictors of survival were histology, lymph node metastases, and the patients' general condition. Stage-for-stage there was no significant difference in survival between tumours of the external and middle ear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1
7

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(50 citation statements)
references
References 12 publications
0
42
1
7
Order By: Relevance
“…Stell proposed a system perhaps better suited to our cases and others, where the primary tumor arises in the middle ear. 3 A tumor starting and staying within the middle ear will be graded T1, which seems more appropriate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stell proposed a system perhaps better suited to our cases and others, where the primary tumor arises in the middle ear. 3 A tumor starting and staying within the middle ear will be graded T1, which seems more appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…For SCC the association with chronic discharge has been reported since Politzer's textbook in 1883. 3 It is suggested that the chronic inflammation that arises from this may cause squamous metaplasia and eventually lead to neoplastic change. There is also a suggestion that viral infection by human papillomavirus may be an aetiological factor.…”
Section: Introductionmentioning
confidence: 99%
“…Hieraus leitet sich entsprechend der Klassifikation von Stell [27] (mod. Hieraus leitet sich entsprechend der Klassifikation von Stell [27] (mod.…”
Section: Klinik Und Intratemporales Wachstumsverhaltenunclassified
“…Hinsichtlich der TNM-Klassifikation werden Einteilungsvorschläge von Pascher [23] und Stell [27] angegeben, die sich auf die Infiltration von Knorpel und Knochen, auf die Beteiligung des N. facialis und schließlich auf den durch bildgebende Diagnostik (CT, MR) feststellbaren Befall benachbarter Regionen -über das Ursprungsorgan hinaus -wie Background and Objective. The symptoms and microscopic findings in carcinoma of the external auditory meatus are often unspecific and misinterpreted as recurrent otitis externa.A definite diagnosis is therefore often delayed, frequently resulting in advanced tumor stages with unfavorable prognosis at the time of diagnosis.…”
unclassified
“…1). Die Tumorstadien lagen in 18 Fällen in fortgeschrittenen Stadien T 2 und T 3 nach Stell [9] vor, in 2 Fällen handelte es sich um Tumoren im Frühstadium T 1 als Zufallsbefunde. Das Alter der Patienten lag im Durchschnitt bei 57 Jahren (48 ± 69 Jahre), wobei Frauen (n = 13) fast doppelt so häufig wie Männer (n = 7) betroffen waren.…”
Section: Ergebnisseunclassified